Research in cohesion and washing off of contamination particles gravitational cleanser precipitating plates - Терьохін, В. І.; Пузік, С. О.; Манзій, B C.; Шевчук, В. С. (Proceedings of National Aviation University (archive), 1998)
Determined is the regime of liquid movement in gravitational cleanser (GC). Conditions are established for absence of washing off the contamination particles from the precipitating plates of the GC